Utilization of Cassava as Substitues of Wheat Flour for Common Carp Diets - Mokoginta, Ing; Priyo Utomo, Nur Bambang; Akbar, A.D.; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2003)
A triplicate experiment was conducted to evaluate cassava (Manihot esculenta) meal as alternative carbohydrate source for wheat flour in the diet of common carp (Cyprinus carpio L.). The diet contained 0%, 25%, 50%, 75%, and 100% of wheat flour were replaced by cassava meal in five treatment groups. Three fishes with 13.33 ±1.69 g initial body weights were cultured in a 50x40x35 cm aquarium for 40 days. Fish were fed on these diets three times a day at satiation. The study showed that growth rate, protein retention, lipid retention and feed efficiency of fish fed diets containing cassava meal up to 50% substitution levels were significantly (p